Comprehensive Review of the Utility of Dynamic Contrast-Enhanced MRI for the Diagnosis and Treatment Assessment of Spinal Benign and Malignant Osseous Disease - Saha, Atin; Gibbs, Haley; Peck, Kyung K.; Yildirim, Onur; Nilchian, Parsa; Karimi, Sasan; Lis, Eric; Kosović, Vilma; Holodny, Andrei I. (American Journal of Neuroradiology, 2024)
Conventional MRI is currently the preferred imaging technique for detection and evaluation of malignant spinal lesions. However, this technique is limited in its ability to assess tumor viability. Unlike conventional MRI, dynamic contrast-enhanced (DCE) MRI provides insight into the physiologic and hemodynamic characteristics of malignant spinal tumors and has been utilized in different types of spinal diseases. DCE has been shown to be especially useful in the cancer setting; specifically, DCE can discriminate between malignant and benign vertebral compression fractures as well as between atypical hemangiomas and metastases. DCE has also been shown to differentiate between different types of metastases. Furthermore, DCE can be useful in the assessment of radiation therapy for spinal metastases, including the prediction of tumor recurrence. This review considers data analysis methods utilized in prior studies of DCE-MRI data acquisition and clinical implications.AIFarterial input functionAUCarea under the curveDCEdynamic contrast-enhancedEESextravascular extracellular spaceHD-IGRThigh-dose image-guided radiation therapyKepexchange rate constantKtranspermeability constantPDprogressive diseaseSCIspinal cord injurySPGRspoiled gradient recalledTICtime intensity curveVeextracellular volume fractionVpplasma volume